Distribution Institution Of Subsidized Fuel For Fishermen In Kangkung Village, Bandar Lampung City - Sitanggang, Rostuti Lusiwati; Damai, Abdullah Aman; Supono, Supono; Riantini, Maya; Tresiana, Novita; Febryano, Indra Gumay (Universitas Bangka Belitung, 2025)
The distribution of subsidized fuel for fishermen is largely determined by government regulations and policies. A well-implemented distribution institution ensures that subsidized fuel reaches fishermen appropriately. This study aims to analyze the institutionalization of subsidized fuel for fishermen in Kangkung Village, Bumi Waras District, Bandar Lampung City. The approach used is a qualitative approach with a case study method. Data collection through in-depth interviews, participatory observation and documentation studies. Data processing is carried out to analyze the institutionalization of subsidized fuel distribution for fishermen. The results of the study indicate that fishermen who use diesel fuel obtain subsidized diesel fuel at fishermen's fuel station according to the provisions set by the Downstream Regulatory Agency Committee Oil and Fuel. Not all fishermen can meet the required provisions. This causes there are still fishermen who cannot access subsidized diesel fuel for their business needs. Fishermen who use Pertalite also cannot freely access subsidized pertalite at the fuel station due to less supportive institutional governance. Thus, it is still necessary for the government to improve regulations so that distribution is more effective and controlled, so that subsidized fuel can be accessed evenly by small fishermen.